Impact of The Covid-19 Pandemic on Teaching Learning Activities - Agus Miftakus Surur; Fitria Zulfa Annurrida (Institut Agama Islam Negeri Jember, 2022)
Learning is an area that has been impacted by Covid-19. Learning is done online to stop the spread of the Covid-19 virus. Efforts have also been made based on the studies mentioned earlier, so this research seeks to provide other alternatives that can be done when learning is in this pandemic season. This research was conducted by reviewing the previous literature as a library, such as from journals, books, and other sources related to learning in the pandemic era. The focus of the research is on learning subjects in the school environment. Learning in several places has been going well. However, in certain places, there are still shortcomings due to some facilities that have not been fulfilled, such as areas that can affect the presence of signals and students' abilities which can be carried out with immediate and direct solutions. To overcome problems that allow students always to follow the learning process, immediate solutions can be carried out by parties related to education, such as school teachers, students, and parents. Meanwhile, indirect solutions are carried out by stakeholders such as the government and local officials to issue policies that can help facilitate education both formally and non-formally.